Drying kinetics and quality aspects during heat pump drying of onion (Allium cepa L.) - Nihar Ranjan Sahoo; Uma Sankar Pal; Sanjaya Kumar Dash; M.D. K. Khan (International Journal of Food Studies)
A prototype heat pump dryer has been developed for drying of fruits and vegetables at low temperature and relative humidity to maintain the quality of dried product. Onions, of Nasik red variety were peeled, trimmed and sliced to 2 mm thickness. The onion slices were dried in the heat pump dryer at 35ºC (32 % R.H.), 40ºC (26 % R.H.), 45ºC (19 % R.H.) and 50ºC (15 % R.H.). Samples were also dried in a hot air dryer at 50ºC (52 % R.H.) for comparison. The drying rate increased with increase in drying air temperature, associated with reduced R.H., in the heat pump dryer. Drying took place mainly under the falling rate period. The Page equation, resulting in a higher coefficient of determination and lower root mean square error, better described the thin-layer drying of onion slices than the Henderson and Pabis equation. Heat pump drying took less drying time of 360 min and yielded better quality dried product, with higher retention of ascorbic acid and pyruvic acid and lower colour change, as compared to a hot air dryer at the same drying air temperature of 50ºC.